Trade and exchange along the Adriatic Sea in Early Imperial times: the case of African imports - Dobreva, Diana (Rei Cretariae Romanae Fautorum Acta, 2023)
During the 1st and 2nd centuries AD it is already possible to notice an interesting presence of African products in the northern Adriatic area. The development of this phenomenon assigns Africa a fundamental role in the Mediterranean market and lays the basis during the 4th century AD for real economic, social, and cultural globalisation of the ancient world. Taking into consideration these trade relationships, the role of Aquileia inside the Adriatic distribution system has been examined. The city occupied a strategic position as a natural terminal of the commercial routes coming from the south and as a redistribution knot towards the hinterland to the provinces beyond the Alps.